List of doctoral research expertise at UiTM Sarawak - Joseph, Corina (Universiti Teknologi MARA, Sarawak, 2007)
The List of Doctoral Research Expertise at UiTM Sarawak (2007) compiles the profiles of academic staff with doctoral qualifications and their respective research fields. It highlights diverse areas of expertise including accounting, management, education, and linguistics. This list reflects UiTM Sarawak's academic strength and its commitment to fostering multidisciplinary research excellence within the university community.